2003
DOI: 10.1002/ange.200390300
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis as a Resource in the Discovery of Potentially Valuable Antitumor Agents: Cycloproparadicicol

Abstract: Durch eine hoch konvergente Synthese gelang die Herstellung einer Reihe von Epimeren und Analoga von Radicicol (1). Biologische Tests offenbarten eine bis dahin nicht bekannte Korrelation zwischen der Stereochemie und dem Potenzial dieser Verbindungen als Tumortherapeutika. So zeigt Cycloproparadicicol (2) vielversprechende therapeutische Eigenschaften, die auf ihrer Chaperon‐inhibierenden Wirkung beruhen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 30 publications
0
42
0
1
Order By: Relevance
“…This renewed interest in radicicol prompted further work on its total synthesis notably by the Lett group [13,14] and the Danishefsky group [15] as well as studies to define the structure-activity relationship of this potential therapeutic. [16][17][18][19][20] Pearl and co-workers showed that despite the lack of structural similarity between radicicol and ATP, radicicol was a competitive ligand for the ATP binding site of HSP90. [21] More recently, a third natural product, novobiocin (3, Figure 1), has also been shown to inhibit HSP90, though through a different binding site.…”
Section: Introductionmentioning
confidence: 99%
“…This renewed interest in radicicol prompted further work on its total synthesis notably by the Lett group [13,14] and the Danishefsky group [15] as well as studies to define the structure-activity relationship of this potential therapeutic. [16][17][18][19][20] Pearl and co-workers showed that despite the lack of structural similarity between radicicol and ATP, radicicol was a competitive ligand for the ATP binding site of HSP90. [21] More recently, a third natural product, novobiocin (3, Figure 1), has also been shown to inhibit HSP90, though through a different binding site.…”
Section: Introductionmentioning
confidence: 99%
“…15,[51][52][53][54][55] The reported potencies for geldanamycin against eukaryotic cell lines range between 20 nM and 5 mM, 19,45,51,56 and the observed variability has been shown to be both methodology-dependent as well as cell line dependent. 57 Geldanamycin-based analogues compete with ATP/ADP for binding to the ATP-binding pocket of Hsp90. 58 The binding affinity (K d ) of geldanamycin (1) for the N-terminal domain of yeast Hsp90 is 1.2 mM, 59 and the crystal structure of geldanamycin bound to its N-terminal Hsp90 binding pocket has highlighted unique structural changes that occur at the binding interface.…”
Section: Geldanamycinmentioning
confidence: 99%
“…Indeed, Danishefsky has shown that merely inversion of the epoxide stereochemistry leads to a 40-fold drop in the activity of the compound. 57 Replacement of the epoxide with a cyclopropyl ring as in cycloproparadicicol, 11, induced a lower penalty than inverting the stereochemistry of the epoxide, dropping the IC 50 B8-fold (20 nM vs. 160 nM) (Figure 2.9, 11). The inclusion of a cyclopropyl ring was a significant improvement as it provided a potent yet stable inhibitor.…”
Section: Direct Analogues Of Radicicolmentioning
confidence: 99%
See 1 more Smart Citation
“…Um dieses Problem zu lösen, entwarfen wir das Analogon Cycloproparadicicol, das anstelle des Epoxids eine stabilere Cyclopropyleinheit enthält. [24] Ein interessanter Schritt in der Synthese von Cycloproparadicicol ist die Ringschlussmetathese-Sequenz zum Aufbau von C5 (Schema 6).…”
Section: Radicicoleunclassified